2016
DOI: 10.4012/dmj.2015-360
|View full text |Cite
|
Sign up to set email alerts
|

Initial cytotoxicity assays of media for sulfate-reducing bacteria: An endodontic biopharmaceutical product under development

Abstract: This study assessed the cell viability of the inoculation vehicle of BACCOR (a combination of sulfate-reducing bacteria plus a culture media for bacteria), a biopharmaceutical product under development for dental use as aid in fractured endodontic file removal from the root canal. Different culture media for bacteria were evaluated: modified Postgate E (MCP-E mod), Modified Postgate E without Agar-agar (MCP-E w/Ag), Postgate C with Agar-agar (MCP-C Ag) and Postgate C without Agar-agar (MCP-C w/Ag). Cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…This biopharmaceutical is still under development to aid in the removal of fractured endodontic files from root canals. Previous studies have demonstrated that D. desulfuricans and D. fairfieldensis are capable of promoting biocorrosion of endodontic files [ 10 ], and cytotoxicity tests have shown that the inoculation vehicle (used in this work) is biocompatible [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This biopharmaceutical is still under development to aid in the removal of fractured endodontic files from root canals. Previous studies have demonstrated that D. desulfuricans and D. fairfieldensis are capable of promoting biocorrosion of endodontic files [ 10 ], and cytotoxicity tests have shown that the inoculation vehicle (used in this work) is biocompatible [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 60-day immersion period was chosen for the study based on the reports of Isa et al [ 17 ] that the SRB in anaerobic reactors were most active between 11 and 24 days after which the activity decreased with a reduction in sulfide production after 50 days as a supersaturation with FeS2 will inhibit the further corrosion of steel [ 18 ]. The corrosive property of SRB has been experimentally elicited by other authors like Heggendorn et al [ 4 , 19 ] who showed the biofilm interaction with the metallic surface of endodontic files and the consequent corrosion. The results of our study are in line with their study wherein we identified localized corrosion induced by SRB of genus Desulfovibrio in stainless steel brackets and wires, NiTi, TMA wires, and Titanium mini-implants.…”
Section: Discussionmentioning
confidence: 97%
“…TDN is a type of nitrate‐reducing, sulfide‐oxidizing bacteria that can induce the biological oxidation of sulfide while reducing the nitrate to nitrogen in anaerobic condition (Qiu et al , 2015). During growth, TDN produces nitrites, oxynitride, NO 2 , NO, N 2 O and nitrogen while also secreting extracellular enzymes and polysaccharides (Heggendorn et al , 2016). When TDN is apoptosis, the enzyme is released due to cell rupture.…”
Section: Introductionmentioning
confidence: 99%